Legal Accountability Of Doctors In Conducting Virtual Health Services (Telemedicine) - Olivia Julita; Erikson Sihotang; Ni Ketut Wiratny (International Journal Labs, 2024)
The regulations or legal basis for telemedicine regulations in Indonesia are contained in Law Number 17 of 2023 concerning Health and Minister of Health Regulation Number 20 of 2019 concerning the Implementation of Telemedicine Services Between Health Service Facilities and Minister of Health Decree Number 489 of 2021 concerning Telemedicine During the Covid-19 Pandemic . The legal responsibilities of doctors in providing virtual health services (Telemedicine) are civil, criminal and administrative legal responsibilities, while professional responsibilities will be followed up in accordance with the procedures in the medical code of ethics.